2005
DOI: 10.1007/s11199-005-2679-0
|View full text |Cite
|
Sign up to set email alerts
|

When Gender Differences Surpass Cultural Differences in Personal Satisfaction with Body Shape in Israeli College Students

Abstract: This study was designed to examine influences of gender and cultural background on participants' satisfaction with body-shape. Participants were Jewish and Arab university students (104 men and 96 women), who completed the Figure Rating Scale (Fallon & Rozin, 1985). Discrepancy between current and ideal figures was used to measure body satisfaction. As in the U.S., women, in comparison with men, were significantly less satisfied with their bodies. They exaggerated the magnitude of thinness that they thought me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…One of the cross-cultural comparisons brought up in the second theme, a study of body dissatisfaction in three different regions in China, showed that people who lived in the modern and westernized city of Hong Kong were more dissatisfied with their bodies than people who lived in the non-westernized and economically less wealthy mountainous region of Hunan (Lee & Lee, 2000). Another study, one of the comparisons between United States and Israel, showed that Israeli people may differ in their levels of body dissatisfaction depending on their religious affiliation (in this case depending on whether they were Jewish or Arab) (Safir et al, 2005). More specifically, it was found that Jewish females were more dissatisfied with their bodies than the Arab females, a finding which the authors attributed to the higher identification with Western culture among the Jewish females.…”
Section: Detailed Descriptions Of the Cultural Groupsmentioning
confidence: 99%
“…One of the cross-cultural comparisons brought up in the second theme, a study of body dissatisfaction in three different regions in China, showed that people who lived in the modern and westernized city of Hong Kong were more dissatisfied with their bodies than people who lived in the non-westernized and economically less wealthy mountainous region of Hunan (Lee & Lee, 2000). Another study, one of the comparisons between United States and Israel, showed that Israeli people may differ in their levels of body dissatisfaction depending on their religious affiliation (in this case depending on whether they were Jewish or Arab) (Safir et al, 2005). More specifically, it was found that Jewish females were more dissatisfied with their bodies than the Arab females, a finding which the authors attributed to the higher identification with Western culture among the Jewish females.…”
Section: Detailed Descriptions Of the Cultural Groupsmentioning
confidence: 99%
“…Similarly, Arab society still stresses values of modesty in women and does not highly value physical appearance [19], although modern perceptions of body image are beginning to penetrate [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that females were significantly dissatisfied with the size and shape of their bodies. Therefore, females are easily prone to body image issues (37). Additionally, the results demonstrated a significant difference in aggression between males and females with MS.…”
Section: Discussionmentioning
confidence: 78%